Analysis of Learning Difficulties in Arabic among Grade Ten Students at Sunan Ampel Integrated Islamic Senior High School Jombang - Sukisno; Musyafa'ah, Lili; Pradita, Kaila Innes Ayu; Ihsan, Muhammad; Kaserero, Subira (Journal of Arabic Language Studies and Teaching, 2026)
Language learning difficulties are a condition that reflects the gap between the expected competencies and the actual ability of students to master the linguistic aspect. This study aims to identify the form of difficulty in learning Arabic and analyze the factors that affect it in grade 10 students at Sunan Ampel Jombang Integrated Islamic High School. The research uses a qualitative approach with a case study design. Data was collected through classroom observation, in-depth interviews, and document analysis involving 10 students and 1 Arabic teacher. Data analysis is carried out using data condensation, data presentation, and conclusion drawn. The results of the study show that the main difficulty of students lies in low vocabulary mastery which has an impact on limitations in understanding texts and developing language skills. This difficulty is influenced by internal factors, such as low motivation and high language anxiety, as well as external factors in the form of limited learning media, less varied teaching methods, and lack of supporting facilities.